PHYSICAL ACTIVITY AS A LIFESTYLE INTERVENTION IN METABOLIC DYSFUNCTION-ASSOCIATED STEATOTIC LIVER DISEASE (MASLD): A NARRATIVE REVIEW OF HEPATIC AND CARDIOMETABOLIC OUTCOMES - Szot, Anna; Babicz, Michał; Chudzicki, Kamil; Czyżewski, Wiktor; Danielczyk, Daria; Malatyńska, Natalia; Műller, Oliwer; Pałubska, Jagoda; Rosa, Katarzyna; Słoma, Agata (International Journal of Innovative Technologies in Social Science, 2026)
This narrative review synthesizes current evidence on physical activity and structured exercise in adults with metabolic dysfunction-associated steatotic liver disease (MASLD), with particular emphasis on aerobic exercise, resistance training, and high-intensity interval training (HIIT). The manuscript was prepared as a structured review of guideline documents, systematic reviews, meta-analyses, randomized controlled trials, and selected observational studies identified primarily through PubMed-based searching and full-text source analysis. Because the overlap between historical non-alcoholic fatty liver disease (NAFLD) and current MASLD populations is nearly complete, earlier NAFLD exercise studies were treated as directly relevant to present-day MASLD. The reviewed literature shows that exercise consistently reduces liver fat, improves cardiorespiratory fitness, enhances insulin sensitivity, and favorably modifies body composition and selected cardiovascular risk markers, often without clinically significant weight loss. Aerobic exercise remains the best-studied modality, but resistance training also appears effective and may be especially valuable in patients with low fitness or concern about muscle loss. HIIT seems feasible and potentially beneficial in selected patients when appropriately supervised. Evidence for direct histological or fibrosis-specific benefit is promising but less robust than the evidence for steatosis and cardiometabolic outcomes. Overall, the findings support physical activity as a central lifestyle intervention in MASLD and highlight the importance of individualized prescription, adherence support, and technology-assisted delivery in future practice.